2016
DOI: 10.1186/s12875-016-0464-5
|View full text |Cite
|
Sign up to set email alerts
|

Impact of IPDE-SQ personality disorders on the healthcare and societal costs of fibromyalgia patients: a cross-sectional study

Abstract: BackgroundData is lacking on comorbid personality disorders (PD) and fibromyalgia syndrome (FMS) in terms of prevalence, and associated healthcare and societal costs. The main aim of this study was to assess the prevalence of PD in FMS patients and to analyse whether the presence of comorbid PD is related to worse functional impairment and greater healthcare (medical visits, drug consumption, and medical tests) and societal costs.MethodsA cross-sectional study was performed using the baseline data of 216 FMS p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
28
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(30 citation statements)
references
References 37 publications
2
28
0
Order By: Relevance
“…Table 1 summarizes the results from the 10 reviewed articles, in descending chronological order. Obsessive-compulsive PD was found to be the most common in three samples (Rose et al, 2009;Uguz et al, 2010;Pando Fernández, 2011), Avoidant PD was the most common in two samples (Fu et al, 2015;Gumà-Uriel et al, 2016), Histrionic PD was the most common in two samples (Cerón Muñoz et al, 2010;Kayhan et al, 2016), and Borderline PD was the most common in one sample (Thieme et al, 2004). Two studies did not report the prevalence of specific PDs (Martinez et al, 1995;Garcia-Fontanals et al, 2014).…”
Section: Resultsmentioning
confidence: 99%
“…Table 1 summarizes the results from the 10 reviewed articles, in descending chronological order. Obsessive-compulsive PD was found to be the most common in three samples (Rose et al, 2009;Uguz et al, 2010;Pando Fernández, 2011), Avoidant PD was the most common in two samples (Fu et al, 2015;Gumà-Uriel et al, 2016), Histrionic PD was the most common in two samples (Cerón Muñoz et al, 2010;Kayhan et al, 2016), and Borderline PD was the most common in one sample (Thieme et al, 2004). Two studies did not report the prevalence of specific PDs (Martinez et al, 1995;Garcia-Fontanals et al, 2014).…”
Section: Resultsmentioning
confidence: 99%
“…Some personality disorders appear to be more prevalent in FMS patients than in the general population, including obsessive-compulsive personality disorder,115,116 borderline personality,94 avoidant personality disorder,117,118 and histrionic personality disorder 115. Some studies have observed a predominance of certain personality traits in FMS, such as perfectionism,119,120 alexithymia,84,121 neuroticism,27,122,123 psychocitism,123 avoidant personality traits,115,117,118 and type D personality124 (which combine high negative affect with social inhibition) 125…”
Section: Personality Temperament Character and Fibromyalgiamentioning
confidence: 99%
“…Extraversion in FMS is associated with lower levels of pain, anxiety, and depression, and better mental health, thereby constituting a protective influence against FMS 45. In general, the presence of personality disorders and negative personality traits in FMS is associated with poorer results after pain treatment,128,129 a worsening of the functional status, higher health care demands (particularly in terms of increased number of medical visits), and greater occupational and medical costs 118,130…”
Section: Personality Temperament Character and Fibromyalgiamentioning
confidence: 99%
“…In three studies [ 35 , 36 , 39 ], participants were selected from previously used databases. Ten studies clearly used the ACR criteria to select participants with FM; in one study the participants were described as people who meet the ACR criteria, without other specifications [ 37 ], 7 referring to ACR criteria of 1990 [ 2 , 3 , 6 , 23 , 25 , 29 , 39 ] and only 3 used the 2010 criteria [ 28 , 38 , 30 ].…”
Section: Resultsmentioning
confidence: 99%
“…Regarding Aspects of Personality The examined studies focused on various aspects of personality associated with FM and highlighted different roles for these aspects compared to FM. Five articles used the term “personality traits” to identify specific psychopathological elements in FM patients, pointing out the role of personality disorders, anxiety, depression as characteristics of a subgroup of patients [ 35 - 37 , 40 , 41 ]. Other studies examined some specific personality traits such as alexithymia, type D personality, emotional regulation, neuropsychological aspects and dysfunctional beliefs, and used a comprehensive model of personality such as that of Eysenck, Cloninger or the big-five model.…”
Section: Resultsmentioning
confidence: 99%